ANALISIS PENGGUNAAN APLIKASI LIVEWIRE DALAM SIMULASI RANGKAIAN ELEKTRONIK DALAM PEMBELAJARAN - Mutia Salwa Defira (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
The main focus of this research is actually simple: to determine how much influence Livewire software has on students' conceptual understanding, motivation, and engagement when learning electronic circuit simulations. Coincidentally, we sampled 81 D3 Electronic Engineering students from Sriwijaya State Polytechnic. We used a descriptive quantitative method. All field data was collected through pre-tests, post-tests, Likert-scale questionnaires, and direct observation during class. The obtained figures were then calculated using descriptive statistics to find average scores and percentages. From this, it's clear that the students responded very positively to Livewire. Interestingly, they found the software easy to operate, made previously complicated theories more understandable, and stimulated their enthusiasm for learning. The classroom atmosphere also became less boring because it was more interactive. Most importantly, their test scores improved after using Livewire. However, honestly, this research still has shortcomings. We haven't had the opportunity to compare Livewire with other similar simulation applications, and after all, the visualization on a computer screen is bound to be different from the actual conditions when holding the equipment in the lab. In essence, Livewire is an excellent starting point for learning electronics simulations. We recommend making this application a mandatory component or a bridge before students are actually involved in practical work in the laboratory.